The Combined Influence of Lower Band Chorus and ULF Waves on Radiation Belt Electron Fluxes at Individual L‐Shells. Issue 5 (2nd May 2021) - Simms, Laura E.; Engebretson, Mark J.; Rodger, Craig J.; Dimitrakoudis, Stavros; Mann, Ian. R.; Chi, Peter J.
Abstract: We investigate the timing and relative influence of VLF in the chorus frequency range observed by the DEMETER spacecraft and ULF wave activity from ground stations on daily changes in electron flux (0.23 to over 2.9 MeV) observed by the HEO‐3 spacecraft. At each L ‐shell, we use multiple regression to investigate the effects of each wave type and each daily lag independent of the others. We find that reduction and enhancement of electrons occur at different timescales. Chorus power spectral density and ULF wave power are associated with immediate electron decreases on the same day but with flux enhancement 1–2 days later. ULF is nearly always more influential than chorus on both increases and decreases of flux, although chorus is often a significant factor. There was virtually no difference in correlations of ULF Pc3, Pc4, or Pc5 with electron flux. A synergistic interaction between chorus and ULF waves means that enhancement is most effective when both waves are present, pointing to a two‐step process where local acceleration by chorus waves first energizes electrons which are then brought to even higher energies by inward radial diffusion due to ULF waves. However, decreases in flux due to these waves act additively. Chorus and ULF waves combined are most effective at describing changes in electron flux at >1.5 MeV. At lower L (2–3), correlations between ULF and VLF (likely hiss) with electron flux were low. The most successful models, over L  = 4–6, explained up to 47.1% of the variation in the data. Plain Language Summary: Low‐frequency electromagnetic waves in the Earth's radiation belt are associated with immediate (same day) decreases in the electron population, but appear to increase the number of electrons 1–2 days later. This is most prominent in the outer radiation belt, at an equatorial distance of 4–6 Earth radii. Key Points: VLF and ULF waves are associated with same day electron (>1.5 MeV) decreases but with flux enhancement 1–2 days later ULF waves are nearly always more influential than chorus, but electron enhancement is most effective when both wave types are present Both VLF and ULF waves are more influential at L 4–6 than at lower altitudes